Enseigner la démarche d’enquête par « le terrain » : transposition didactique en formation initiale d'enseignants - Sylvie Joublot Ferré (Recherches en Éducation)
The introduction of the Plan d'Etudes Romand for primary schools in French-speaking Switzerland in 2012 has given geography teaching a new framework and new directions. As a result, initial teacher training in this subject has had a direct impact on its content and methods. We propose to report on an experiment conducted in tertiary education, as a teacher and researcher in geography and didactics, over several years at the Haute École pédagogique de Lausanne, a teacher training institution in the canton of Vaud. In this article, we propose to evaluate the didactic added value of teaching field research from the point of view of learning. The aim is not, therefore, to present research, but rather to propose a way of carrying out didactic transposition with reference to the content and methods of university geography, considering other factors such as the context, the audience and the targeted professional skills in particular.